Family Behavior in Caring for People with Mental Disorders During Covid-19 - Daulay, Wardiyah; Nasution, Mahnum Lailan; Sri Eka Wahyuni; Sitorus, Pranciska (Caring: Indonesian Journal of Nursing Science, 2021)
Mental disorder is a serious health problem. It is a chronic disease that requires long healing. The factors of education, information, income, and stigma experienced by family can avoid the behavior in caring people with mental disorders that has been carried out. Thus, it impacts the care and treatment given to them. The purpose of this systematic review is to identify family behavior in caring for people with mental disorders during Covid-19. This study was conducted with a systematic method by reviewing the literature obtained from Google Scholar, Sciencedirect, PubMed, Proquest and Research Gate. Three keywords were used to get some relevant literature. As a result, the author obtained eight literature matching the author's criteria made by using the systematic review method. The most affecting factor for healing quality of people with mental disoder is their family's action in caring them. Health education is very influential on family's knowledge. Educational factor and information determine family behavior in seeking treatment. Providing adequate information and health education about mental disorders for families is necessary to avoid any faults while seeking medical assistance.